FOREIGN EXPERIENCE OF USING CLOUD SERVICES FOR THE INFORMATION-ANALYTICAL SUPPORT OF THE ORGANIZATION OF INTERNATIONAL COOPERATION OF UNIVERSITIES - Kravchenko A. (Kherson State University, 2017)
Foreign experience of using cloud services for the information-analytical support of the organization of international cooperation of universities is presented in the article. The best practices of using cloud services like new analytical tools and platforms for solving complex problems of optimization of the management of scientific and international activities of universities are analyzed. Architecture of the cloud computing environment as a system is analysed; it consists of 4 blocks: hardware; infrastructure; platforms and applications and cloud taxonomy for the organization of the scientific, academic and international activities of the University support, as well as taxonomy of the main cloud technologies to support the University's academic and international activities. The activities of the leading universities of the world for 2016-2017 are monitored and the expert results of Quacquarelli Symonds specialists' are presented according to the World University Ratings. The evaluation was carried out based on more than 50 different indicators, such as: academic reputation; employer's reputation; faculty / student rate; reference (quotation) about the faculty; international correlation of faculties; international student rate; assessment of the quality of researches of scientists and determination of productivity of the university; number of quotes; graduate university rewards; assessment of teaching quality; employment opportunity; Internationalization, which includes statistical indicators for the number of foreign students styding at University; number of exchange students; number of international partnership Agreements with other universities; accessibility; the possibility of distance learning; social responsibility; innovation; art and culture; inclusiveness, etc.